The role of emotional engagement and mood valence in retrieval fluency of mood incongruent autobiographical memory - Greenberg, Jonathan; Meiran, Nachshon (Frontiers in Psychology, 2014)
Background: Retrieval of opposite mood autobiographical memories serves emotion regulation, yet the factors influencing this ability are poorly understood. Methods: Three studies examined the effect of mood valence (sad vs. happy) and degree of emotional engagement on fluency of mood incongruent retrieval by manipulating emotional engagement and examining the effect of emotional film clips on the Fluency of Autobiographical Memory task. Results: Following both sad and happy film clips, participants who received emotionally engaging instructions exhibited a greater recall latency of the first opposite mood memory, and had generated less such memories than those receiving emotionally disengaging instructions (Studies 1 and 2). A happy mood induction resulted in recollection of fewer mood incongruent memories compared to a sad mood induction. Providing emotionally engaging instructions was found to specifically hinder mood incongruent retrieval, without impairing mood congruent retrieval (Study 3). Conclusion: High emotional engagement seems to impair the retrieval of mood incongruent memories. Being in a happy mood may also partially impair such retrieval. Implications regarding emotional regulation are discussed.